Evaluasi Level Kinerja Bangunan Gedung Kayu Bertingkat Rendah Akibat Beban Gelombang - Yosafat Aji Pranata; Fadlillah Ariani Suroso; Bernardinus Herbudiman (Universitas Islam 45, 2021)
Several coastal areas in Indonesia are at risk of moderate to high tsunami disasters, this is related to the condition that Indonesia is located in an earthquake high risk area. At this time there are many buildings located on the coast with a low-rise stilt house system with the main structural system, namely beams and columns using timber materials. The building structure design includes the performance evaluation process, namely strength, stiffness and structural stability. The purpose of this research is to study the evaluation behavior of performance levels, especially the strength and stiffness of low-rise timber buildings, namely the level of structural performance due to gravity and lateral loads, namely sea waves. The research scope is a three-story building with a beam and column frame structure system. Columns are circular and beams have a square cross section. The loads taken into account are gravity and lateral. The strengths discussed are the bending capacity of the beam and the compressive capacity of the column. In order to obtain building behavior that is closer to real conditions, especially in beam-column joints, secondary data is used, namely empirical data on the envelope load-deformation curve of the beam-column joint test results in the laboratory (modeled as link property). Evaluation of structural performance begins with structural analysis using SAP2000 software, to obtain internal forces and building drift. The results show that the use of link properties in beam-column joint joints in the timber building structures shows greater deformation results compared to rigid joint models, this indicates that modeling the structure with beam-column joint joints modeled as link property has an impact on building stiffness. Lower and represents the condition of a timber building with beam-column joint characteristics closer to the actual condition. The existence of a hole size in the column (to insert the beam) which is larger than the cross-sectional size of the beam results in the rotation of the joint not being zero and a slip occurs when the joint works to transmit internal forces.